The combined effects of moisture and temperature on the microbial load of poultry fat - Kufahl, Taylor; Johnson, Adam; Magossi, Gabriella; Jiao, Suinian (My University, 2017)
Salmonella spp. has been linked to rendered animal fat used in pet food industry. Companies have to use test-and-hold procedures in order to determine the safety of the product. This can be costly and lead to reprocessing. The purpose of this research was to determine the effects of moisture levels and storage temperatures on the growth of Salmonella in rendered poultry fat. Three different moisture levels were tested: 0.5%, 1%, and 3%. The combined effect of a wet contamination method at low 2.3x10^5 CFU/mL and high 5.8x10^8 CFU/mL inoculum with different storage temperatures (21˚C and 48˚C) was evaluated. Wet inoculation mimicked cross contamination from moisture. A control was held with no added water for both the high and low inocula at each storage condition. Poultry fat was stored for seven days, and every day an aliquot was sampled. An enrichment procedure was performed in order to account for injured and damaged cells. Samples were then plated on XLD agar and incubated at 37˚C for 24 hours. Results obtained from this study showed that when storing the fat at 22˚C there is no significant decrease in the growth of the Salmonella, while a significant effect on the growth of the pathogen was observed at higher temperature.
Keywords: Spring 2017